Paraparetic Variant of Guillain-Barré Syndrome in First 24 Hours of Postpartum Period: A case report - Aljaafari, Danah (Sultan Qaboos Univ Med J, 2020)
Guillain-Barré syndrome (GBS) is a heterogeneous disorder with a diverse clinical presentation ranging from weakness of certain body regions to tetraparesis with autonomic dysfunction and respiratory failure. Paraparetic GBS is a variant of GBS which is characterised by weakness limited to the lower limbs only. It is crucial to identify such topographical presentations, as a delay in diagnosis can lead to delayed initiation of specific treatment, which can negatively impact the outcome. We report a 29-year-old female patient who presented to the King Fahd Hospital of the University, Al Khobar, Saudi Arabia, in 2017 with rapid onset asymmetrical weakness of lower extremities associated with bladder dysfunction during the immediate postpartum period. The weakness spared cranial nerves and arms and imaging studies of the spine was unremarkable. Cerebrospinal fluid investigations showed cyto-albuminologic dissociation and nerve conduction studies showed features of demyelination. The patient was diagnosed with a paraparetic variant of GBS and treated with intravenous immunoglobulin. She had almost recovered completely at the two–month follow-up.